Informing FAO’s global agri-food system analysis: A research protocol for tracking climate-change adaptation. Enhancing national adaptation plans and investments. - Nowak, Andreea C.; Njuguna, Lucy; Rosenstock, Todd (2024)
Climate-Action researchers have developed a protocol that has informed the upcoming global update report on agrifood systems within Nationally Determined Contributions (NDCs) developed by the United Nations’ Food and Agriculture Organization (FAO). The Protocol provides a comprehensive guide for assessing countries’ climate-change adaptation plans, including goals, objectives, actions, and indicators for tracking progress. In adopting the Protocol, FAO is considering critical priorities for investments in agrifood systems and pathways that will enhance existing and future national policies.